Natural selection on gene function drives the evolution of LTR retrotransposon families in the rice genome - Baucom, Regina S.; Estill, James C.; Leebens-Mack, Jim; Bennetzen, Jeffrey L. (Genome Research, 2009)
Although the proliferation of LTR retrotransposons can cause major genomic modification and reorganization, the evolutionary dynamics that affect their frequency in host genomes are poorly understood. We analyzed patterns of genetic variation among LTR retrotransposons from Oryza sativa to investigate the type of selective forces that potentially limit their amplification and subsequent population of a nuclear genome. We performed both intra- and interfamily analyses of patterns of molecular sequence variation across multiple LTR retrotransposon genes. This analysis involved more than 1000 LTR retrotransposon sequences from 14 separate families that varied in both their insertion dates and full-length copy numbers. We uncovered evidence of strong purifying selection across all gene regions, but also indications that rare episodes of positive selection and adaptation to the host genome occur. Furthermore, our results indicate that LTR retrotransposons exhibit different but predictable patterns of sequence variation depending on their date of transposition, suggesting that LTR retrotransposons, regardless of superfamily and family classifications, show similar “life-histories.”